Repeated sex chromosome evolution in vertebrates supported by expanded avian sex chromosomes - Sigeman, Hanna (Proc Biol Sci, 2019)
Sex chromosomes have evolved from the same autosomes multiple times across vertebrates, suggesting that selection for recombination suppression has acted repeatedly and independently on certain genetic backgrounds. Here, we perform comparative genomics of a bird clade (larks and their sister lineage; Alaudidae and Panuridae) where multiple autosome–sex chromosome fusions appear to have formed expanded sex chromosomes. We detected the largest known avian sex chromosome (195.3 Mbp) and show that it originates from fusions between parts of four avian chromosomes: Z, 3, 4A and 5. Within these four chromosomes, we found evidence of five evolutionary strata where recombination had been suppressed at different time points, and show that stratum age explained the divergence rate of Z–W gametologs. Next, we analysed chromosome content and found that chromosome 3 was significantly enriched for genes with predicted sex-related functions. Finally, we demonstrate extensive homology to sex chromosomes in other vertebrate lineages: chromosomes Z, 3, 4A and 5 have independently evolved into sex chromosomes in fish (Z), turtles (Z, 5), lizards (Z, 4A), mammals (Z, 4A) and frogs (Z, 3, 4A, 5). Our results provide insights into and support for repeated evolution of sex chromosomes in vertebrates.